Preliminary socio-economic impact assessment of Sibalom Natural Park as community-based tourism site Sibalom, Antique - Gelvezon, Princess (University of the Philippines in the Visayas, 2007)
The study was undertaken to assessthe socio-economic impact of Sibalom Natural Park as a community-based Tourism Site in Barangay Igpanolong and Baranagy Imparayan, Sibalom, antique. Generally, it aimed to assess the present socio-economic condition of the people with regard to the establishment of SNP as a site for Community-based Tourism. The study used Key Informant Interview, Focused Group Discussion and Secondary Data to gather necessary data and information. Open-ended interview was used for the K11 as well as tables for FGD. The respondents and participants were the selected Barangay Officials, Bantay Gubat, and Household Heads, who were available during the scheduled date for data gathering. The study found out that SNP brought changes on the socio-economic well being of the people in Barangay Igpanolong and Barangay Imparayan. It provided aabundant source of water for irrigation system, which contributes to the perceived increase of agricultural production, thus creating extra income. increase of income gave youth the opportunity for a higher education. It also offered more livelihood opportunities taht caused people outside the community to transfer and reside in the said barangays. Moreover, SNP helped improved the health condition of the local poeple because of clean water and fresh air, more and wonderful sites for recreation, and a more secured environment against man-made and natural disasters. SNP provided benefits to the local people but these were not enough to improve living condition of the community. Herein, researchers recommended the following: 1. provide economic support to local people ; 2. establishment of infrastructure such as roads, school building, cottages and local market ; 3. provide health services like medical mission as well as personnel and medicines ; 4. massive information campaign with regards to environmental laws and ordinances ; and 5. develop framework for community-based tourism.